Propuesta de un sistema de gestión integral de residuos sólidos domiciliarios mediante un modelo de mejora continua en el distrito de quiruvilca - Carranza Rengifo, Ezaine Ramiro (2011)
The research was based on a proposal to develop a comprehensive management system of household waste through continuous improvement model Quiruvilca district. By having determined the existence of two social strata B and C levels, were determined for representative samples characterization study, using 30 samples per level. We used the technique of direct observation, quantification was done by calculating gravity. The overall composition of organic solid waste was 6,32%, 7,58% Inorganic and 86,10% inert. 100% of identified solid waste paper, cardboard, wood, plastic bags, bottles, cans, synthetic fabrics, rubber and others. The classification of solid waste from non-compacted waste in the municipal dump Quiruvilca City, was characterized by the 86,10% of waste generated in both social levels of ash.